Pengawasan Legislatif Melalui Hak Penyidikan dalam Kerangka Konstitusi Indonesia - Ridwan Syaidi (Jurnal Hukum Lex Generalis, 2025)
The right of inquiry is the right of the House of Representatives (DPR) to conduct investigations into the implementation of laws and/or government policies related to important, strategic matters that have broad impact on social, national, and state life, which are suspected to be contrary to statutory regulations. The purpose of this research is to analyze the use of the DPR's Right of Inquiry conducted against government policies related to the Implementation of the 2024 General Elections. The type of legal research used is normative legal research or library legal research, which is a type of legal research obtained from library studies, by analyzing legal problems through statutory regulations, literature, and other reference materials related to the problem. The results of this research explain that doctrinally, the governmental system is a system that explains the relationship/relations between holders of executive power and holders of legislative power, and in carrying out its constitutional functions, the DPR has the right of interpellation, the right of inquiry, and the right to express opinions. Both in Parliamentary and Presidential systems, the right of inquiry is one form of manifestation of legislative oversight authority over the executive as the holder of governmental power. This oversight is directed at holders of executive power because it is the executive that carries out day-to-day governance, both the implementation of governance that is directly derived from or constitutes a mandate of laws and the implementation of governance that constitutes the implementation of policies made by the executive itself.